Adoption of 3G services among Malaysian consumers: an empirical analysis - Chong, Alain Yee Loong; Darmawan, Nathan; Ooi, Keng Boon; Lin, Binshan (Inderscience Enterprises Ltd, 2010)
The purpose of this study is to analyse the factors influencing the usage of 3G technology in Malaysia. By extending the Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI) model, this study found that perceived advantages, perceived ease of use, variety of service and social influence are able to predict the adoption of 3G among Malaysian consumers. This study allows 3G service providers to understand which factors influenced the usage of 3G in Malaysia. Other developing countries that plan to deploy 3G can also formulate business strategies using the results from this study.